Treatment Choices in Women with Bipolar Disorder Seeking Pregnancy: A Clinical Case Illustration - Barbui, Corrado; Bertolazzi, Andrea; Hanife, Batul; Cipriani, Andrea (Case Reports in Psychiatry, 2013)
After ten years of successful maintenance treatment with lithium and olanzapine, a 40-year-old woman with bipolar disorder expressed concerns about continuing the use of medicines, as she was planning a pregnancy. In the past, she had suffered from five severe manic episodes with hospital admissions. After consultations with the treating psychiatrist, gynaecologist, and family doctor, olanzapine was stopped and lithium was gradually withdrawn. After few months, the patient, still in treatment with lithium 300 mg/die, experienced a new manic episode with hospital admission. Treatment with lithium and olanzapine was restored, and she progressively recovered. This case suggests that the risk of manic recurrence after ten years of maintenance treatment may be as high as the well-known risk of recurrence after few years of maintenance treatment, a consideration that doctors may find useful in the light of a complete absence of evidence on treatment choices after five years of successful maintenance treatment.